Targeting Gay Men in the Luxury Industry: An Exploratory Study - vallee, cindy (2008)
Despite the increasing interest of luxury marketers in the gay population, very little is known about the characteristics or values defended by this community. Further, the nature of the relationship between gay men and luxury goods has never been investigated. Based on the fact that the successful design and development of marketing strategies depends upon an in-depth knowledge of the population studied, this research intends to identify the shared values and meanings of luxury goods consumption of the gay subculture and their impact on the effectiveness of printed luxury brands advertisements in gay publications. Focus groups were held as a research method as they are particularly relevant to exploratory researches. The findings related to the gay subculture highlighted the impact of the greater acceptance of this community by the mainstream culture on the shared values and meanings of consumption, thus challenging some of the conclusions drawn by the main researcher in the area, namely Steven M. Kates. It also appeared that some of the values highlighted in the first part of the research had a significant impact on the consumption of luxury goods. Finally, the level of transferability of these values to advertising messages has been tested. They concluded on a greater attractiveness of the advert where the most superficial meanings were represented (e.g. physical appearance). It further appeared that the purchase intention was rather influenced by a greater visibility of the product and perception of quality. Ultimately, this study led to the generation of two models related respectively to the luxury goods consumption in the gay subculture and the meanings and characteristics impacting on the effectiveness of printed advert. It is suggested that these models will be useful for marketers to refine their strategies directed towards the gay market.